Artificial accelerated ageing of GFRP pultruded profiles made of polyester and vinylester resins: characterisation of physical-chemical and mechanical damage - Cabral-Fonseca, S. (2013)
This article presents results of experimental investigations on the durability of glass-fibre-reinforced polymer (GFRP) pultruded profiles exposed to typical environments of civil engineering applications.